Making Mends: Visibly Mending the Circular Economy - van Kaathoven, Danika; Huffman, Emma; Mizuno, Daijiro (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper introduces the Making Mends Workshop, a workshop format centering on the practice of visible mending as a means to explore broader notions of repair and care in the context of the Circular Economy. The workshop is structured into three parts: a reflective exercise that encourages participants to consider the practical and conceptual meanings of mending, a brief lecture and practice session that provides basic knowledge and skills of visible mending, followed by the participants repairing a personal item. Findings suggest the potential impacts of the visible mending workshop as a catalyst for fostering user agency through skill acquisition and meaning-making. The workshop highlights visible mending as a communal repair practice supporting the Circular Economy by extending product life and preserving material and emotional value. The notion of Mending for Others was identified as a valuable addition to communal repair, where repair strategies benefit from social interactions that involve sharing knowledge and skills, care, and joy, ultimately leading to durable repairs.